2020
DOI: 10.1371/journal.pone.0232370
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury in critically ill cancer patients is associated with mortality: A retrospective analysis

Abstract: Background In critically ill patients, acute kidney injury (AKI) is common and associated with short-and long-term complications. Our objectives were to describe the epidemiology and impact of AKI in cancer patients admitted to the Intensive Care Unit (ICU). Methods We identified all patients with a haematological malignancy (HM) or solid tumour (ST) who had an emergency admission to the ICU in a tertiary care centre between January 2004 and July 2012. AKI was defined according to the KDIGO criteria. Results 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…In patients with solid tumors, only serum creatinine had independent prognostic impact in addition to platelet count. This finding in cancer patients with solid tumors is in line with many other studies on a variety of critically ill patients showing that decreased renal function is associated with worse outcome [37,38].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In patients with solid tumors, only serum creatinine had independent prognostic impact in addition to platelet count. This finding in cancer patients with solid tumors is in line with many other studies on a variety of critically ill patients showing that decreased renal function is associated with worse outcome [37,38].…”
Section: Resultssupporting
confidence: 91%
“…Furthermore, this study demonstrates that a relevant number of patients (8%) received vv-ECMO despite progression of their malignant disease at the time of ECMO initiation. The decision to initiate vv-ECMO in this setting is intriguing given that tumor progression is generally associated with a poor prognosis [ 36 38 ]. This study confirms that progressive disease indicates a very poor prognosis (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…15 Therefore, we provide evidence from demographic data regarding the prevalence and risk factors of AKI among patients with newly diagnosed APL. Because the etiology of AKI is significantly associated with the 6-month complete response rate and 28-day mortality, 9 , 16 Identifying patients who are at risk of developing AKI during induction chemotherapy is essential.…”
Section: Discussionmentioning
confidence: 99%
“…A recent multicenter, observational study showed that 15% of patients admitted to European ICUs have cancer, with solid tumors being more common than hematological cancer (85% vs. 15%, respectively) [ 18 ]. AKI is a severe and frequent complication during critical illness ranging from 54% [ 19 ] to 70% [ 20 , 21 ], and it is particularly common in patients with hematological cancer or multiple myeloma [ 18 , 22 ]. Notably, in most cases, AKI is already present on admission to ICU rather than acquired in ICU [ 21 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…AKI is a severe and frequent complication during critical illness ranging from 54% [ 19 ] to 70% [ 20 , 21 ], and it is particularly common in patients with hematological cancer or multiple myeloma [ 18 , 22 ]. Notably, in most cases, AKI is already present on admission to ICU rather than acquired in ICU [ 21 ]. However, reports vary depending on the criteria used to define AKI [ 23 ].…”
Section: Epidemiologymentioning
confidence: 99%